Antioxidant Activity Test of Tampoi Fruit Peel Extract (Baccaurea pyriformis Gage) using the DPPH (2,2-Difenil-1-Pkrihidrazil) Method - Novi Milasari; Reksi Sundu Reksi Sundu; Hayatus Sa’adah Hayatus Sa’adah; Stevani Olivia Stevani Olivia; Ghina Adhila; Nurul Fatimah (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Excessive oxidation reactions in the body can cause various harmful effects, mainly due to the uncontrolled production of free radicals. Antioxidant compounds are needed to protect the body from free radical attacks. One natural source of antioxidants is the tampoi fruit (Baccaurea pyriformis Gage). This fruit is known to contain metabolites such as flavonoids, phenolics, tannins, and saponins, which act as natural antioxidants. The purpose of this study was to determine the antioxidant activity of tampoi fruit peel (Baccaurea pyriformis Gage) using the DPPH method. This was an experimental study with the independent variable being ethanol extract of tampoi fruit peel and the dependent variable being antioxidant activity. The research stages included plant determination, slimpisia preparation, maceration extraction, phytochemical screening, determination of extract moisture content, and antioxidant activity testing with DPPH. The results showed a drying shrinkage of 5.6%, an extract yield of 13%, and an extract moisture content of 14.77%, which is classified as a thick extract. Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, and saponins. Antioxidant test results showed that tampoi fruit peel ethanol extract had an average IC value of 11.8165 ppm (very strong category), and vitamin C as a comparison had an IC value of 7.5019 ppm. Thus, tampoi fruit peel ethanol extract has strong antioxidant activity.